Pervasive detachment faults within the slow spreading oceanic crust at the poorly coupled Antilles subduction zone - Boris Marcaillou (Nature Portfolio, 2021)
Pervasive detachment faults in the oceanic basement at the NE Antilles Subduction Zone could enable deep fluid circulation and serpentinization and partly control the reduced interplate seismicity, according to seismic reflection and bathymetric data